(untitled) (TEST Ticontre. Theory Text Translation, 2024)
The article reflects on the presence of pedophile subjects and scenes of child sexual abuse in Walter Siti’s works. Referring to the principle of overdetermination repeatedly enunciated by the writer, the textual function that these representations assume from time to time is investigated. The choice to speak unconventionally about pedophilia and abuse is framed within Siti’s conception of realism, the ethical value of which is problematized. L’articolo riflette sulla presenza di soggetti pedofili e scene di abuso sessuale su minore nelle opere di Walter Siti. Facendo riferimento al principio della surdeterminazione più volte enunciato dallo scrittore, viene indagata la funzione testuale che assumono di volta in volta queste rappresentazioni. La scelta di parlare in modo non convenzionale di pedofilia e abuso viene inquadrata nella concezione del realismo di Siti, di cui viene problematizzata la valenza etica.